PsycEXTRA Dataset 2011
DOI: 10.1037/e696122011-001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ethnic Identity in Participatory Processes That Facilitate Psychological Empowerment Among Urban Youth

Abstract: The current study involved the development and testing of a path model to predict psychological empowerment for urban youth ages 13-17. Data from a survey of urban youth in a city in the northeast United States were analyzed to test the model. The variables included in the model were: perceived neighborhood problems, neighborhood sense of community, social support, participation in community and school activities, and ethnic identity. Utilizing structural equation modeling, survey data were analyzed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Diemer and Li (2011) found that parental and peer support was directly related to youth's perceptions of sociopolitical control and participation in social action. Similarly, Tamanas (2010) found that social support from peers, friends, family, and other important adults was directly related to psychological empowerment and that social support mediated the relationship between perceived neighborhood problems and psychological empowerment. In addition, Ozer and Schotland (2011) found that youth with higher levels of psychological empowerment reported having more caring relationships with adults at school and more support from peers at school.…”
Section: Supportive Adults and Peer Relationshipsmentioning
confidence: 89%
See 2 more Smart Citations
“…Diemer and Li (2011) found that parental and peer support was directly related to youth's perceptions of sociopolitical control and participation in social action. Similarly, Tamanas (2010) found that social support from peers, friends, family, and other important adults was directly related to psychological empowerment and that social support mediated the relationship between perceived neighborhood problems and psychological empowerment. In addition, Ozer and Schotland (2011) found that youth with higher levels of psychological empowerment reported having more caring relationships with adults at school and more support from peers at school.…”
Section: Supportive Adults and Peer Relationshipsmentioning
confidence: 89%
“…Furthermore, Watts et al (2002) stated that indoctrination must be avoided-that youth cannot be told how to think. In addition, Tamanas (2010) found that the ability to perceive problems in one's environment was positively linked to the development of psychological empowerment for youth of color. It should be noted that inquiry-based learning is a critical component of the CCI curriculum-As part of CCI, students work together to identify a problem that affects them in their schools, design and carry out a research project to explore that problem, and then engage adults in their school in conversations about a proposed solution to their problem.…”
Section: Inquiry-based Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth of color who experience supportive relationships from adults and peers seem to experience increased personal empowerment (Hipolito-Delgado & Zion, 2015). Tamanas (2010) found a direct relationship between personal empowerment and social support from peers, friends, and family. Furthermore, Ozer and Schotland (2011) found that youth with higher levels of personal empowerment reported caring relationships with adults and support from peers.…”
Section: Supportive Relationshipsmentioning
confidence: 99%
“…Critical consciousness is a likely first step in the process of personal empowerment, as the awareness of oppression is thought to inspire sociopolitical action (Carr, 2003;Tamanas, 2010). The development of critical consciousness requires an understanding of how sociopolitical, cultural, and historical forces contribute to the oppression of marginalized communities (Watts, Abdul-Adil, & Pratt, 2002).…”
Section: Critical Consciousnessmentioning
confidence: 99%